Membranoproliferative glomerulonephritis and Pott's disease - Ram, Rapur (Clin Kidney J, 2014)
The reports of glomerular lesions of kidney due to tuberculosis are sparse. A 48-year-old gentleman, presented with swelling of feet of 3 months duration. As he had renal impairment, proteinuria and normal-sized kidneys, he was subjected to renal biopsy. The light microscopy and immunofluorescence revealed the diagnosis was membrano-proliferative glomerulonephritis. During hospital stay, the patient complained fever and stiffness at thoracic spine. The MRI of thoraco-lumbo-sacral spine revealed paravertebral abscess at D11–D12. The pus aspirated was positive for Mycobacterium tuberculosis. He was started on anti-tuberculous medication. After 8 weeks of therapy, the serum creatinine was 1.5 mg/dL and 24 h urine protein 250 mg.